Soil microbial community structure and soil fertility jointly regulate soil microbial residue carbon during the conversion from subtropical primary forest to plantations - Fandi Xu; Cong Li; Yanxuan Chen; Jiangchong Wu; Haidong Bai; Shaoguang Fan; Yuchun Yang; Yanping Zhang; Shuaifeng Li; Jianrong Su (Geoderma, 2024)
Soil microbes mediate soil organic carbon (SOC) storage by affecting microbial residue carbon (C) in terrestrial ecosystems, a main source of SOC. However, how microbial residue C accumulation changes during the conversion of subtropical primary forest to plantations and the role of soil microbial community structure in regulating these changes remain unclear. Here, effects of conversion from forest on microbial residue C accumulation in three plantations, including tea (Camellia sinensis var. assamica), walnut (Juglans regia), and macadamia (Macadamia integrifolia). We assessed amino sugars content and the relative importance of soil microbial community structure, soil fertility, and aboveground biomass in four forest types in southwest Yunnan province, China. Our results show that total microbial residue C accounted for 27.8 % of SOC on average across all forest types, and fungal residue C contributed more to SOC than bacterial residue C across different forest types. Conversion from primary forest decreased fungal, bacterial, and total microbial residue C content in all plantation types except tea. Microbial residue C contents was significantly lower in the macadamia plantation than in the primary forest and the tea plantation. Fungal and total microbial residue C content increased with increasing soil microbial community composition, soil fungal abundance, and soil fertility. Soil fertility regulated fungal, bacterial, and total microbial residue C accumulation, which was major determinant of microbial residue C via its influence on soil fungal and bacterial abundance. Overall, we found that soil fungal abundance contributed more to microbial residue C accumulation than change in soil microbial community composition. We also found that soil bacterial abundance was negatively correlated with fungal and microbial residue C, while soil fungal abundance was positively related to microbial residue C accumulation. Ascomycota was most important phylum regulating microbial residue C. These findings suggest that soil fungal and bacterial abundance and soil fertility are the principal regulators of microbial residue C accumulation during the conversion from primary forest to different plantations.